Experiments on reconstructing and using T-shaped wooden Spades - Lyngstrøm, Henriette; Olesen, Martin Winther; Overvad, Lucas (Danish Journal of Archaeology, 2024)
Abstract This article summarizes an attempt at reconstructing and using T-shaped wooden spades as well as reflecting on the connection between structures and resource use around Knudmosen near Herning. However, an important limitation on this process is that very few spades are dated. The conclusion is that the spades are relatively easy to produce and well suited to digging peat.